2016
DOI: 10.3389/fphar.2016.00138
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Is Associated with Pain Precipitation and Elevation in DeltaFosb Expression

Abstract: A number of acute or repeated stimuli can induce expression of DeltaFosB (ΔFosB), a transcription factor derived from the fosB gene (an osteosarcoma viral oncogene) via alternative splicing. ΔFosB protein is currently viewed as a ‘molecular switch’ to repeated stimuli that gradually converts acute responses into relatively stable adaptations underlying long-term neural and behavioral plasticity. ΔFosB has received extensive attention in drug addition, depression, and stress adaptation, but changes in ΔFosB pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The MS protocol was conducted as previously described in detail ( Leon Rodriguez and Duenas, 2013 ; Wang et al, 2016 ). Briefly, male and female mice in both the Tlr4 +/+ and Tlr4 -/- strains were mated for litters.…”
Section: Methodsmentioning
confidence: 99%
“…The MS protocol was conducted as previously described in detail ( Leon Rodriguez and Duenas, 2013 ; Wang et al, 2016 ). Briefly, male and female mice in both the Tlr4 +/+ and Tlr4 -/- strains were mated for litters.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently, the specificity of mPFC subregions is receiving more attention [170,[205][206][207][208][209]. In particular, electrophysiological recordings of L5 pyramidal cells reveal relevant functional differences between PrL and IL: the GABA A antagonist bicuculline modulates neuron activity in PrL, whereas cannabinoid receptor CB1 and mGLuR5 are relevant components in IL [22,27,210].…”
Section: The Prelimbic (Prl) and Infralimbic (Il) Corticesmentioning
confidence: 99%
“…The mechanism of visceral hypersensitivity and pain is still poorly understood due to the diverse nature of visceral hypersensitivity compounded by multiple factors such as sexual dimorphism, psychological and physical stresses, genetic and epigenetic traits, and the nature of predisposed disease ( Chen et al, 2015 ; Elsenbruch and Enck, 2016 ). We recently demonstrated that early life stresses, for example, neonatal colorectal distension (CRD), maternal separation, could induce visceral hypersensitivity in rats ( Wang et al, 2016 ; Zhang et al, 2016a , b ). Visceral information is collected by thoracolumbar and sacral spinal visceral afferents, and coded by viscerosomatic neurons in spinal cord, thalamus, limbic system, and cortex ( Larauche et al, 2012 ; Moloney et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%